Penyuluhan Kesehatan tentang Perubahan Fisiologis pada Ibu Hamil di Wilayah Kerja Puskesmas Watopute - Mika Sugarni; Susi Sastika Sumi; Yusnaeni Y; Maryam Jamaluddin (AJAD : Jurnal Pengabdian kepada Masyarakat, 2023)
Pregnancy is a natural process that causes a series of physiological changes in pregnant women. The physiological changes experienced during pregnancy sometimes become a period of vulnerability that requires special attention and vigilance. So that pregnant women need more knowledge about the many changes that can occur to their bodies. The purpose of implementing this community service activity is to provide additional knowledge about physiological changes both physically and organ systems in the body of pregnant women during pregnancy. The approach taken by the team was in the form of health education activities regarding physiological changes in pregnant women which were carried out offline through direct visits to Posyandu. As a result of community service activities, pregnant women feel very helpful because the discomfort that occurs during pregnancy is normal so that mothers do not need to feel anxious and worried.